Pensamiento visual en el proceso de enseñanza y aprendizaje de las aplicaciones del cálculo integral, en estudiantes de programas de ingeniería de la Universidad Antonio Nariño - Sánchez Ossa, Ángela María (Universidad Antonio Nariño, 2021)
Student desertion constitutes today one of the evaluation criteria of Higher Education Institutions, which is why it is of great importance to analyze the causes for which this phenomenon occurs. According to Díaz (2009), desertion generates great economic difficulties for universities, in addition to increasing inequality gaps regarding access and permanence of students in tertiary education. In engineering programs particularly, "academic mortality" becomes latent in the first courses of calculus, especially differential and integral calculus. The high rates of mortality and repetition may be due to the lack of motivation with which the student reaches the university, which is often due to low academic performance in the area of ​​mathematics, as well as the lack of understanding of fundamental mathematical concepts , due to the level of abstraction with which the courses are taught.